Ibuprofen, paracetamol and tilidine; their role in post tonsillectomy pain at Dr George Mukhari Hospital - Makhafula, Lebone D. (University of Limpopo ( Medunsa Campus), 2011)
Background: Tonsillectomy is one of the commonest operations performed by ENT surgeons. Pain, haemorrhage, delayed feeding and resumption of normal activities are common morbidities. Different groups of analgesics are used to reduce these morbidities. Objective: We examined the effectiveness of the use of three analgesics, some in combinations in reducing these morbidities. The primary outcome measures were pain, resumption of normal diet, resumption of normal physical activities and secondary haemorrhage. The secondary outcome was comparison of pain profile of children and adults. Methods: A prospective randomized double blind controlled study. Subjects were recruited and randomized into three study groups; group A (Paracetamol & Ibuprofen), group B (Ibuprofen) and group C (Paracetamol, Ibuprofen & Tilidine). A diathermy dissection technique was used on all patients in removing tonsils. Pain was measured using a patient morbidity scoring form (PMS) as well as the Smiley scale. The care givers for children and adult patients recorded all other events. Results: Sixty five patients were recruited, 30 were in group A, 20 in group B and 15 in group C. There were 36 females and 29 males. The youngest patient was 4 years of age and the oldest was 38 years. The mean number of days prior to resuming normal daily activities for groups A, B and C was 9.27, 10.60 and 7.67 respectively. Group C patients started their daily activities earlier than those in group B (p≤0.05). The average number of days to stop analgesic use was 12.3, 13.3 and 10.6 for groups A, B and C respectively. Patients in group C stopped using analgesics earlier than group B patients (p≤0.05). There was no statistically significant difference in PMS scores, resumption of normal diet, post-tonsillectomy haemorrhage as well as pain profiles of adults and children. Conclusion: Paracetamol-ibuprofen-tilidine combination appears to be more effective than either paracetamol-ibuprofen combination or ibuprofen in the first two weeks in the treatment of post tonsillectomy pain (p>0.05), however, further studies will have to be carried out to confirm this. Patients treated with a paracetamol-ibuprofen-tilidine combination appear to stop medication and return to their normal daily activities much earlier (p ≤ 0.05). Minor haemorrhage from the use of ibuprofen following tonsillectomy was not a cause for concern.
Thesis (M Med(Otorhinolaryngology)) -- University of Limpopo, 2011.
Keywords: Ibuprofen; Tonsillectomy; Tilidine; Paracetamol